Effects of nanoparticles on phase morphology in thin films of phase-separated diblock copolymers. (30th January 2017) - Jehnichen, Dieter; Pospiech, Doris; Friedel, Peter; Horechyy, Andriy; Korwitz, Andreas; Janke, Andreas; Näther, Franziskus; Papadakis, Christine M.; Perlich, Jan; Neu, Volker
Abstract : This study investigates the morphology changes in thin diblock copolymer (DiBCP) films occurring in the interaction with modified nanoparticles (NPs). Magnetite (Fe3 O4 ) and silica (SiO x ) were prepared and used. Poly(pentyl methacrylate-b-methyl methacrylate) (PPMA-b-PMMA) (70/30 mol mol −1, hcp cylinders of the PMMA phase) DiBCP were employed to prepare thin films having thicknesses to realize standing cylinders in pure DiBCP films. The investigations aimed at two topics: (1) morphology after controlled incorporation of organo-modified NP (gold, silver, Fe3 O4, SiO x ) and (2) additional solvent vapour annealing (SVA) with tetrahydrofuran (and chloroform for comparison). The laterally ordered morphology in thin films was examined by GISAXS and atomic force microscopy. Keeping the same type of morphology in nanocomposites, the dimensions of the periodic nanostructure altered depending on type and amount of incorporated NP. It was found that SiO x clusters enlarge the lateral distance of the PMMA cylinders, whereas metallic NPs reduce this parameter. Applying SVA improves the phase separation slightly, whereas lateral distances were kept constant or were reduced a little. Switching of domain orientation upon SVA could not be detected in the presence of NPs located at the polymer/substrate interface.